Flows in Converging Slits and Pipes as Flows with Dominating Extensions - Zahorski, S. (Engineering Transactions, 1988)
The concept of plane and axi-symmetric flows with dominating extensions (cf [1, 2]) is applied to moderately converging flows in slits and pipes. It is shown that many properties of the flows considered essentially depend on the extensional viscosity function as well as its derivative with respect to the extension rate.